2021
DOI: 10.1021/acsanm.0c03373
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tensile-Strained Self-Assembled Ge Quantum Dots on InP Substrates for Integrated Light Sources

Abstract: Highly tensile-strained Ge quantum dots (TS-Ge-QDs) emitting structures with different size were successfully grown on InP substrates by molecular beam epitaxy. Dislocation-free TS-Ge-QDs were observed by transmission electron microscopy. Finite element modeling indicates a maximum tensile strain of 4.5% in the Ge QDs, which is much larger than the required strain to achieve direct band gap conversion of Ge based on theoretical prediction. Photoluminescence (PL) from a direct band-gap-like transition of TS-Ge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The use of DE technology can obtain highly symmetrical quantum dots [26]. In addition, it was confirmed that the controlled growth of quantum dots can be achieved by changing experimental parameters during the growth process of QD, which hugely further expands its development in optoelectronic devices [27][28][29][30][31][32][33]. Although DE method has been proved to be very successful in the controlled growth of QD, there is still some works worth to do.…”
Section: Introductionmentioning
confidence: 90%
“…The use of DE technology can obtain highly symmetrical quantum dots [26]. In addition, it was confirmed that the controlled growth of quantum dots can be achieved by changing experimental parameters during the growth process of QD, which hugely further expands its development in optoelectronic devices [27][28][29][30][31][32][33]. Although DE method has been proved to be very successful in the controlled growth of QD, there is still some works worth to do.…”
Section: Introductionmentioning
confidence: 90%
“…[ 15,16 ] As a result and owing to not only the large lattice mismatch of about 7.7% but also the presence of tensile‐strained Ge nanolayer, GaSb is a preferred candidate as the matrix of highly tensile‐strained Ge. In contrast to the optical advances of Ge in InP matrix, [ 1,13 ] it is unfortunate that the optical and electronic properties of tensile‐strained Ge embedded in GaSb remain unclear, and thus the questions, 1) if light emission from direct‐gap transition does exist and 2) how the thickness of Ge nanolayer influences optoelectronic behavior, call for answers.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Ge nanostructures embedded in latticemismatch III-V group matrix were another strategy introduced to realize highly tensile-strained Ge. [1,4,12,13] For example, a tensile strain of about 5% is reached in the self-assembled Ge/InAlAs quantum dots grown on InP substrate. [14,15] Different from the growth of Ge on InP and/or InAs that follows the the Volmer-Weber mode without Ge wetting layer, Ge embedded in antimonide obeys the Stranski-Krastanov growth mode and a clear tensile-strained 2D nanolayer exists.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum confinement effect was evidenced in small Ge and GeSi NCs 16 – 18 , enabling bandgap engineering along with composition 19 , shape 20 and strain 21 , 22 leading to tuning of optical and photoelectrical properties of NCs.…”
Section: Introductionmentioning
confidence: 99%